Early-stage immunoexpression of inflammatory, angiogenic, and survival markers in tongue epithelium of mice exposed to hookah smoke - Aldini Beuting Pereira; Arieli Carini Michels; Sarah Freygang Mendes Pilati; Filipe Modolo; Ana Paula Camargo Martins; Caroline Busatta Vaz De Paula; Seigo Nagashima; Lúcia Noronha; Ana Clara Prado Fonseca; Ariane Jéssica Torres Turmina; Heloisa Franco De Meira; Luisa Gabriela Carneiro Ramos; et al. (PLoS ONE, 2025)
Objective The objective was to evaluate the early-stage immunoexpression of markers (COX-2, NF-kB, VEGFR-1 and apoptotic index) related to inflammation, angiogenesis, and cell survival in the tongue dorsum epithelium of mice exposed to hookah smoke. Materials and methods The sample consisted of Swiss mice (N = 20), female gender, aged 2 months, and approximately 25g each, four groups (n = 5) mice: group exposed to fresh air and groups exposed to hookah smoke for 7, 15, and 30 days. Tongues were embedded in paraffin. A tissue microarray was constructed, and immunohistochemistry was performed for Cyclooxygenase 2, NF-kappa B, Vascular Endothelial Growth Factor Receptor 1, and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) for apoptotic analysis. The positive and negative cells were quantified in the epithelium of the mid-dorsal tongue region. Kruskal-Wallis and Dunn tests was made. Results The apoptotic index was higher at 30 days of smoke exposure (20.38% basal/ 19.63%/ suprabasal) compared to the group exposed to air (9.55%/ 11.88%), The expression of Vascular Endothelial Growth Factor Receptor 1 was higher at 30 days of smoke exposure (30.15%/ 38.15%) compared to the group exposed to air (18.25%/ 3.60%). Conclusion Hookah smoke induced greater apoptosis and increased expression of Vascular Endothelial Growth Factor Receptor 1 in the epithelium of the tongue at 30 days, potentially playing a role in the initial stages of carcinogenesis, in the early stages of hookah use.